HOW EMOTIONS ARE DEVELOPED: INSIGHTS FROM VYGOTSKY’ AND LEONTIEV’S WORKS - Ahrens, Andreas; Zascerinska, Jelena; Filimonova, Daria; Bikova, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Teacher and learners’ emotions are a significant factor that influences the implementation of adult education. The research aim is to explore the works of Vygostky and Leontiev for modelling the development of emotions in adult education. Theoretical analysis aimed at theory building about emotion development in adult education was applied to the present research. Exploratory type of research was implemented and described in this paper. The present work reflects the insights from the theory of Activity by Leontiev, and the theories of Interiorization, Cultural-historical Activity, and Concept Formation by Vygotsky. The research results in conclusions that teacher’s and learners’ emotions develop in adult education through the educational process. The educational process is gradually implemented in certain sequence. The educational process starts from teaching and external emotions in Phase 1, moves to peer-learning and quasi-emotions in Phase 2, and proceeds further to learning and internal emotions in Phase 3. The inter-connections between intrapersonal and interpersonal levels of emotions were described. The research allows building a theory on emotion development. The research limitations were identified. Directions of further work were proposed.